Formation of motivational mechanisms in small businesses based on theory of generation - S. G. Kamshilov (Путеводитель предпринимателя, 2020)
The article considered the practical aspects of the theory of generation in small businesses. Assemble algorithm determining membership the staff organization’s in generational section on value and age criteria. Formed models of personnel management based on nonmonetary methods.